The collectors - Baldacci, David (New York : Warner Books, 2006)
"The assassination of the Speaker of the House sets the members of the Camel Club in a race to prevent a silent yet bloody coup in Washington"--Provided by the publisher.
Accelerated Reader
Keywords: United States. -- Congress. -- House -- Fiction; Library of Congress -- Fiction; Secret societies -- Fiction; Legislators -- United States -- Fiction; Conspiracies -- Fiction; Stone, Oliver -- (Fictitious character) -- Fiction; Camel Club (Imaginary organization) -- Fiction; Camel Club (Imaginary organization); Conspiracies; Legislators; Secret societies; Stone, Oliver (Fictitious character); Political fiction; Mystery fiction; Suspense ficton; Suspense fiction; Thrillers (Fiction); Fiction; Political fiction; Suspense fiction; Political fiction; Thrillers (Fiction); Suspense fiction